1969
DOI: 10.1002/app.1969.070131106
|View full text |Cite
|
Sign up to set email alerts
|

Load–compression behavior of flexible foams

Abstract: The load–compression behavior of a foam reflects its geometric structure and the physical properties of the matrix polymer. Quantitative relations between these parameters have been established in the present study. Based on both theoretical analyses and experimental data obtained on a flexible polyurethane foam, it is shown that the compressive stress can be factored into the product of two terms: (1) a dimensionless function of the compressive strain, ψ(ε), calculated from experimental load–compression data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

1970
1970
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(56 citation statements)
references
References 7 publications
0
55
0
1
Order By: Relevance
“…[4,8,9] Thornton et al indicated in their research [4] that the efficiency usually reached a maximum at some intermediate strain (about 0.5 to 0.6), and this strain seemed to be irrelevant to the relative density and the matrix composition. Different results were obtained in the present study.…”
Section: Energy Absorption Efficiencymentioning
confidence: 95%
See 1 more Smart Citation
“…[4,8,9] Thornton et al indicated in their research [4] that the efficiency usually reached a maximum at some intermediate strain (about 0.5 to 0.6), and this strain seemed to be irrelevant to the relative density and the matrix composition. Different results were obtained in the present study.…”
Section: Energy Absorption Efficiencymentioning
confidence: 95%
“…There have been several models describing the compressive deformation and mechanical properties of cellular materials, [8][9][10][11] the more recent ones of which are presented by Ashby and Gibson et al [9] They predicted that the compressive stress-strain curve of cellular solids, either elastomeric, plastic, or brittle ones, can be divided into three regions: the linear elastic, the plateau, and the densification. The extent of each region depends on its relative density and responds to different mechanical responses.…”
Section: The Compressive Deformation Models Of Cellular Solid Mamentioning
confidence: 99%
“…An example of a phenomenological model was stated by Rusch. [39][40][41] However, a drawback of the model is its inaccuracy in describing the densification phase when, a consequence of the compression, internal voids progressively disappears. On the other hand, micromechanical models take into account the deformation mechanisms of the cell structure under loading, using several adimensional parameters that reflect these effects.…”
Section: Compression Testsmentioning
confidence: 99%
“…3 Elastic modulus, yield point, 3 and length of stress plateau 4,5 are the main parameters to be considered in foam design for specific applications.…”
Section: Introductionmentioning
confidence: 99%